Pallavi S Mhaske, Shrikrushna Subhash Unhale, Vijaya B Mehetre, Kanchan P Pandhare, Vaishnavi U Petkar, Kailash R. Biyani - Mhaske, Pallavi S; Unhale, Shrikrushna Subhash; Mehetre, Vijaya B; Pandhare, Kanchan P; Petkar, Vaishnavi U; Biyani, Kailash R (Asian Journal of Pharmaceutical Research and Development, 2020)
Parkinson’s disease (PD), or simply Parkinson’s, is a long-term degenerative disorder of the central nervous system that mainly affects the motor system. Parkinson's sickness (PD) has a place with a gathering of conditions called motor system issues, which cause unintended or wild developments of the body. The precise cause of PD is unknown, but some cases are hereditary while others are thought to occur from a combination of genetics and environmental factors that trigger the disease. In PD, brain cells become damaged or die in the part of the brain that produces dopamine--a chemical needed to produce smooth, purposeful movement. Parkinson's ailment is a dynamic sensory system issue that influences development. Indications start progressively, in some cases beginning with a scarcely observable quake in only one hand. Quakes are normal, however the confusion additionally ordinarily causes solidness or easing back of development.In this review article we include Introduction ,How to Parkinson’s disease occurs , mechanism , pathophysiology , Diagnosis , treatment , medication , causes , symptoms of Parkinson’s disease .